Hak Berkeyakinan dalam Tatanan Hukum - Nurainun Mangunsong (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Religious right and faith are fundamental terms in religious life in Indonesia. As a religious community that is in the basic frame of the Pancasila state, then the society must give respect and guarantee protection for the followers of different religions and faiths. Therefore, the faith must be stand in line with religion. If not then the injustice will keep coloring nation's constitutional life of Indonesia and become blurry print as a nation upholds Bhineka Tunggal Ika.